Effectiveness of Bangle Rhizome Extract Gel Spray (Zingiber Purpureum Roxb.) on Healing Perineal Wounds in Postpartum Mothers - Sri Wahyu Aritonang; Suryati Komorowulan; Sri Sumarni (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Childbirth is a physiological process that lead to complications such as perineal lacerations. One alternative to accelerate perineal wound healing is the use of a spray gel bangle rhizome (zingiber purpureum roxb), which has regenerative, antibacterial, anti-inflammatory and antioxidant properties. To determine the effectiveness of bangle rhizome extract spray gel in accelerating perineal wound healing in postpartum mothers. This quantitative study useda True Experimental with a pre-test and post-test control group. A sample of 36 postpartum mothers with second-degree perineal lacerations were divided into two groups: intervention group (bangle rhizome extract gel spray) and control group (dry cleaning treatment). The sampling was conducted using randomized sampling. Analysis used the Generalized Linear Model- Repeated Measures (GLM-RM). The bangle rhizome extract gel spray applied twice daily for 7 days was effective in accelerating perineal wound healing. The GLM-RM test showed a significant decrease REEDA scores in the intervention group (p=0.0000.050), while the control group only experienced a decrease in the posttest on day 7. Bangle rhizome extract gel spray given twice daily for 7 days is effective in accelerating perineal wound healing in postpartum mothers based on REEDA scores.  Keywords: Bangle Rhizome Extract Gel Spray, Perineal Wound, Postpartum Mothers.